ANALISIS PENGARUH KARAKTERISTIK DEWAN TERHADAP KESULITAN KEUANGAN PADA PERUSAHAAN DI INDONESIA - Listari, Dian Ayu; Karina, Ria (Politeknik Negeri Ambon, 2021)
This research generally aims to gain new knowledge and discoveries about the importance of the impact of good corporate governance on the board on financial difficulties to prevent bankruptcy of the company. The research was conducted using a purposive sampling method, with the object of research being companies that have been listed on the Indonesia Stock Exchange. The company must have a complete annual report from 2016 to 2020 and use the rupiah currency. The dependent variable in this study is financial difficulties followed by three independent variables, namely the size of the board of directors, the independence of the board and the activity of the board. There are also control variables in the study in the form of return on equity and solvency ratios. The results of this study indicate that there is a significant positive effect between the size of the board of directors and the company's financial difficulties, the independence of the board does not have a significant effect on financial difficulties and board activities have a significant positive effect on the dependent variable, namely financial difficulties. As the return on equity control variable has a significantly positive effect on financial difficulties, the solvency ratio does not have a significant effect on financial difficulties